Coordinations fines lors des Uchi-Komis (Repetition de la premiere partie d'une projection de judo) - Calmet, M.; Miarka, B.; Franchini, E. (10e JORRESCAM, 2010)
Scientific approach is always rigorous but not necessarily complicated and observation is always a difficult act. Four examples with micro analyses concerning accurate coordinations repeating uchi-komi (entrance or first part of a throw) were analyzed. Tools to collect data are free softwares or free applications and permitted micro measurements with time in milliseconds and distances in mm. Results show: i) on specific uchi komi (i.e. practicing o uchi gari), body of a judo player can be assimilated as a pendulum in which the fixed point is located on the shoulder level. Coordinations are stable during all the repetitions (i.e. shoulder, talon, hips and toe always did the same movement and their trajectories on graphic crossed themselves at the same time. ii) after artificial disturbances about balance (i.e. 10 fast rotations on the ground) or after judo action disturbance (blocking an attack) high level judo player recovered his regularity after 3 or 4 repetitions. Perspectives are to continue the analyses concerning artificial and judo disturbances and to observe how tiredness during training sessions disturb these coordinations.